THE CORRELATION BETWEEN ELECTRIC CURRENT PRODUCED AND THE LIGHT SOURCE DISTANCE IN PHOTOELECTRIC EFFECT EXPERIMENTS - Upik Rahma Fitri; Esmar Budi; Hadi Nasbey; Mira Ziveria; Intan Muhara (Spektra: Jurnal Fisika dan Aplikasinya)
In experimental observations of the relationship between the electric current generated and the distance of the light source on the Planck constant device, it can show a comparison between the electric current generated and the variable distance of the light source. The experimental equipment specifications use the Planck constant experimental set with a 12v/35w tungsten halogen lamp, output 15v, accuracy +-0.2%, power requirement 220V, fuse rating 0.5A and red filter. Experiments using the concept of the photoelectric effect phenomenon begin by irradiating metal materials with constant photon light and then the light passes through a red light filter with a wavelength of 635 nm. The use of a filter is done by placing a 635 nm light filter on the light propagation path to the metal material, so that the light that passes through the filter is only light with a wavelength of 635 nm. The choice of the red filter is due to the fact that the frequency of light with a wavelength of 635 nm can cause electrons to come out of the metal as a result of photons hitting electrons in the metal. After the metal material is irradiated with photon light, the electron charges on the metal will be disturbed and come out of the metal. The movement of these electrons produces an electric current whose value can be seen. By testing distances of 18, 20, 22, 24, 26, 28, and 30 cm, the results of a current value of 0.528 are obtained; 0.382; 0.295; 0.232; 0.182 and 0.154. From these experiments it was shown that the further away the light source, the smaller the electric current generated due to the light. This is because the closer the distance to the light source, the more light intensity hitting the metal, this results in a greater number of photons hitting the metal.